The semantics of clause linkage: analysis of the finite complex complementation types in the English complain verbs - Martín-Padrón, Federico José (Complutense Journal of English Studies, 2023)
This article engages with the semantics of complex finite syntactic linkages of the complain verbs in English, as in Levin (1993). Since these verbs display two main types of complex complementation patterns, this research explains how semantics motivates and predicts to a great extent the clause linkage process through the Interclausal Relations Hierarchy, the Interclausal Semantics Relation Hierarchy, and the Syntactic Interclausal Relations Hierarchy, within the Role and Reference Grammar (RRG) framework. RRG’s solid proposal is employed in this research for the systematization of the syntax-semantics interface of these verbs, drawing two main conclusions. Firstly, the results accommodate and respect the rationale of the Iconicity Principle governing the hierarchy: the closer the semantic bond (indirect discourse > direct discourse), the tighter the syntactic link (clausal subordination (daughter) > sentential subordination (daughter)). And secondly, I argue in favor that sentential subordination (daughter) is the kind of syntactic link prompted by the direct discourse semantic relation, as this has not been fully dealt with within this theory of grammar.